Pengaruh Service Quality Dan Corporate Image Terhadap Customer Satisfaction Dan Customer Loyalty - Shafa Shafira; Indrawati . (LPPM UNIBI, 2020)
The development of the internet at this time is increasing and becoming something that is important and needed by everyone. Internet users in Indonesia continue to increase each year, until the end of 2019 the number of users in Indonesia reached 7.697 million people with 143.3 million internet users, which means it has reached 55% of the total population. As one of the countries that increase internet users the highest in the world. Internet service providers compete to provide the best quality of services such as Indihome. But in that case, Indihome still sought approval, but still sought approval from their company. This study measures customer loyalty and customer satisfaction on indihome fiber by looking at service quality from four variables namely network quality, customer service, information quality, security & privacy and the dimensions of company image or company image by transferring question items to 385 indihome service user samples. The data analysis technique used is SEM with PLS. Based on the test results, service quality, corporate, and customer satisfaction have a positive influence on customer loyalty